Evaluation of joint and muscle function of paediatric upper and lower extremities - Afifi, Mohamed; Abdulazeez, Muhammad Uba; Aminian, Kamiar; Stylianides, Georgios Antoniou; Abdullah, Kassim Abdulrahman (Frontiers in Bioengineering and Biotechnology, 2025)
Road traffic crashes are the leading cause of injuries, disabilities, and fatalities for children and young adults. Extremity joint injuries have been identified as one of the contributing factors to chronic disabilities among children in road crashes. However, our knowledge on the biomechanics of the pediatric upper and lower extremity joints remains limited. Understanding the biomechanics of the upper and lower extremity joints is essential to provide important information for developing enhanced protection against extremity joint injuries for children involved in road crashes. The protocol developed in this study will be used for assessing the following biomechanical properties of the pediatric upper and lower extremity joints: 1) active and passive ranges of motion (AROM and PROM), 2) muscle strength, and 3) joint stiffness. The joints included in the protocol are shoulder, elbow, wrist, hip, knee and ankle. Joint-specific settings and testing procedures are provided for assessing the range of motion (ROM) using goniometry and the muscle strength as well as joint stiffness using isokinetic dynamometry. A sample of 200 healthy children will be recruited from selected schools in Al Ain city, United Arab Emirates for the assessment. Descriptive statistical analyses will be conducted to characterize the biomechanical properties with regards to age, gender, and ethnicity. To determine the influence of anthropometric and demographic factors on ROM, strength, and stiffness, a series of multiple regression analyses will be performed to identify the factors that best predict ROM, strength, and stiffness.